Stem cell control through tailored ion release profiles from resorbing calcium phosphate materials - De Melo, Nigel (2020)
Control of stem cell fate has been traditionally enacted by applications of proteins, cytokines, and small molecules. Recent studies suggest that inorganic ions can similarly influence stem cell behaviour and fate. Phosphate based glasses (PBGs) demonstrate tailorable dissolution rates for the local release of these ions, demonstrating potential for both hard and soft tissue regeneration. PBG microspheres have been proposed as a promising biomaterial for orthopaedic applications due to their chemical similarity to the inorganic phase of bone and the potential for their ionic dissolution products to promote bone healing and repair. This project explored the effects of ionic dissolution products on human mesenchymal stem cells (hMSCs) in vitro and how they may be used to control stem cell fate.